Del Convento al Mundo - María Paula Castillo (Medievalista)
Medieval religious orders implemented a series of devices to control the behavior of their members. In the case of the Order of Friars Minor, the systematization of the general constitutions that regulated the life of the brothers came with the generalship of Fray Buenaventura. The behavior of the friars that was standardized affected the interior and exterior spatiality of the convents. The aim of this article is to analyze to what extent the behavior of the friars is regulated and conditioned in the directives given by the chapter; as well as to establish which are the main spheres of interference on the movement of the friars between the conventual space and the outside and what guidelines of conduct and punishment are established.